Organization and development of the design process in the world practice - Shumak, Ljudmila; Filippov, Oleksandr (Ways to Improve Construction Efficiency, 2023)
The process of design, or project execution, can formally be viewed as the development of a prototype or prototype of a proposed or possible object or its state. The design process is based on professional knowledge, achievements in science, technology, technological advances, and mathematical methods for solving engineering problems, the basics of art, economics, pricing policy, inventive activity, regulations, legislation and much more. The beginning of the design is determined by the presence of the main provisions on the proposed object and the sources of its financing. As a result, investment feasibility studies and other studies are usually carried out prior to project development. There are relevant rules for the selection of projects, tenders are considered and the documents are finally approved. Design includes many systems, as well as the knowledge of engineers - this is an integral part of the overall investment process, the main participants of which are the Investor, the Customer, the construction department (Contractor) and the design company. Abroad, design is one of the most important stages in the implementation of urban development projects. Studies have shown that about 15% of the project budget is spent on correcting design errors, and more than 50% of project changes are due to poor design in the early stages [1, 2]. This article analyzes the design process in various foreign countries, such as the USA, Great Britain, France, Germany, Singapore, Bulgaria, based on publicly available materials (regulatory documents, tender documentation, guidelines, websites of architectural bureaus and official websites of regional and city administrations). The approach to determining the cost of architectural design for the conclusion of work contracts is considered in two ranges: 1) Range of territory – documents containing development projects for elements of the planned structure of the city. Architectural and urban planning concepts, depending on the type of documentation adopted in the country; 2) Development range (buildings) – a document that defines the development project for the elements of the planned structure of the city, as well as architectural, functional, technical and constructive solutions for capital construction projects. Depending on the type of document adopted in the country, it can be draft, design or working. The study of foreign practice of organizing the process of architectural and construction design has revealed a number of principles that can guide the authorities in ensuring high quality in the development and implementation of urban development projects.